O CONTROLE DIFUSO DE CONSTITUCIONALIDADE E OS INSTRUMENTOS DE AMPLIAÇÃO DOS SEUS EFEITOS: garantidores da integridade ou elementos de contenção do acesso à justiça - Salem Neto, José Murilo Duailibe (2015)
The present research studies the diffused constitutionality control, specifically through the Extraordinary Appeal, and its possibility to be a warrant of rights as integrity, against the changes that expanded its effects, as well as implemented institutes that also changed its admissibility requirement. In that order, is exposed how the constitutional supremacy ideal was accomplished, based on the constitutionalism of fundamental rights and the assignment of constitutional States of right. Highlighting the legitimacy arguments of the constitutionality control, especially for the warrant of fundamental rights, as well as analyzes the origination of this instrument and its history on the brazilian State. Highlighting the functions of the recent changes on the diffused constitutionality control, in a analyzis about the hard relation between the warrant of integrity and the rationalization of the judicial protection, with the creation of access requirements.